Edukasi Pemanfaatan Uwi (Dioscorea Alata L.) sebagai Pencegah Osteoporosis pada Ibu Menopause di Kelurahan Sumber Karya, Binjai - Ismedsyah, Ismedsyah; Sihombing, Jhonson P. (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2023)
Menopausal women's health needs to be a concern. Menopausal women experience a cessation of estrogen production. The function of estrogen helps the formation of bone osteoblasts. As a result of the cessation of estrogen production in menopausal women, osteoporosis will occur. Plants that have phytoestrogens are Uwi (Dioscorea alata L.). Uwi has the potential to maintain the bone density of rats experiencing osteoporosis because there is a decrease in the number of osteoclasts. To introduce to mothers in the Sumber Karya Sub-District - Binjai, Uwi is used to treat osteoporosis. The method is in the form of educating mothers about the use of Uwi as a prevention of osteoporosis. The activity began and ended with the distribution of questionnaires to measure mothers' knowledge about menopause, osteoporosis and how to prevent osteoporosis. The results of education are an increase in scores before education 71%, after education 97%. In conclusion, the education of mothers in Sumber Karya Binjai Village understands the benefits of Uwi in treating osteoporosis Keyword : Uwi, Osteoposis, Menopausal, women